(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The interaction between workers and employers inside the corporate environment is industrial relations. Industrial relations also involve the mechanisms by which those relationships are articulated (such as collective bargaining, involvement of employees in decision-making and resolution of claims and disputes) and, where applicable, conflict management between employers, staff and labor unions. It involves the research and experience of collective bargaining, trade unionism and partnerships with labor management. This paper relates to study of industrial relations in SSI with special reference to HSIIDC(Sonipat), 75 respondents had been picked on basis of simple random sampling technique.